2020
DOI: 10.3389/fpsyg.2020.01620
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mat Exergaming to Improve the Physical Performance, Cognitive Function, and Dual-Task Walking and Decrease the Fall Risk of Community-Dwelling Older Adults

Abstract: Physical exercise and cognitive training were previously demonstrated to improve the physical functioning and decrease the incidence of falls for older adults. This study aimed to utilize an interactive exergame mat system to develop a novel cognitive–physical training program and explore the training effects on physical performance, cognitive function, dual-task walking (DTW), and fall risk compared to the control condition. In this quasi-experimental non-randomized controlled intervention study, 110 communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 38 publications
1
28
2
1
Order By: Relevance
“…In this study, a fall refers to an event that results in a person coming to rest inadvertently on the ground or floor or other lower level. The 12-item fall risk questionnaire (FRQ) was used to evaluate risk factors associated with falls, such as history of falls, fear of falling, gait and balance problems, leg muscle weakness, impaired sensation and proprioception, depression, and side effects of medications [ 12 , 19 ]. It was developed based on evidence and has clinical acceptability, and it was found to have good concurrent validity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, a fall refers to an event that results in a person coming to rest inadvertently on the ground or floor or other lower level. The 12-item fall risk questionnaire (FRQ) was used to evaluate risk factors associated with falls, such as history of falls, fear of falling, gait and balance problems, leg muscle weakness, impaired sensation and proprioception, depression, and side effects of medications [ 12 , 19 ]. It was developed based on evidence and has clinical acceptability, and it was found to have good concurrent validity.…”
Section: Methodsmentioning
confidence: 99%
“…The handgrip strength of participants’ dominant hands was assessed using a hand dynamometer (TTM-YD, Tokyo, Japan). Participants were asked to stand with their arms by the side of the body and were given verbal encouragement to give their maximum effort [ 12 ]. The best value of two trials with 1-min breaks was taken.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These elements create dual task situations [i.e., Thinking while moving situations, (Herold et al, 2018)], in which the player needs to focus on two or more things simultaneously. Strikingly, few studies investigated the effects of exergames on dual-task performance [for noticeable exceptions, see (Schättin et al, 2016;Peng et al, 2020)] but, recently, Gallou-Guyot et al ( 2020) compared (indirectly) conventional MCDT training and exergaming. They did not observe any superiority of the latter over the former, though some studies suggested the opposite [e.g.…”
Section: Are Exergames Effective For Enhancing Brain Plasticity and Cognition?mentioning
confidence: 99%
“…Gait performance was measured under three conditions in a random order based on a random number table: (1) walking (single task); (2) walking while verbally counting backward in decrements of three from a random number between 90 and 100 (cognitive dual-task walking); and (3) walking while carrying a tray (size: 38 × 28 × 5 cm 3 ) that was 80% full of water (motor dual-task walking). In line with a previous study, 26 our dual-task walking testing protocol comprised cognitive and motor dual-tasks because in their daily life, people tend to combine walking and executing a cognitive or motor task.…”
Section: Methodsmentioning
confidence: 68%